Discussion of deep–seated structures as plumbing systems of hydrothermal minerals using gravity and magnetic data from the West Qinling Orogenic Belt - Fan, Zhenyu; Xiong, Shengqing; Yang, Hai; Fan, Zhengguo; Li, Fang; Ge, Tengfei; He, Jingzi; Jia, Zhiye (Frontiers in Earth Science, 2024)
The West Qinling Orogenic Belt (WQOB) in central China records the tectonic evolution and deep geodynamics process associated with plate collision on the northeastern margin of the Qinghai-Tibet Plateau. The study of the deep-seated West Qinling stucture is beneficial for revealing the evolution of the West Qinling crust during the continental collision orogeny, and also has significance for mineral exploration. In this study, the crustal structure and the distribution of major faults in the West Qinling Orogen are calculated by processing geophysical aeromagnetic and ground gravity data. The density and magnetic susceptibility differences between the West Qinling crust and the upper mantle are calculated by fitting, and the depth and trend of the faults related are inferred from the gravity and magnetic inversion results.The geophysical results can provide new evidence for inferring the deep-seated geological crustal structure in the West Qinling Orogenic Belt. It provides the support of gravity and magnetic cognition results for the overall subduction of the lower crust of Ruoergai to the West Qinling Orogenic Belt. It is indicated that the formation of the Diebu-Sanhe fault may have a strong correlation with the Mianlue suture zone, and their intersection may penetrate into the lower crust at a depth of about 50 km or more.The West Qinling structure represents important conduits for migrating magmaticderived hydrothermal fluids. During the continental collision, the West Qinling major faults provided hydrothermal migration channels for ore-forming materials in different tectonic periods. Meanwhile, multiple the geological activities led to the formation of mineral deposits related to magmatic hydrothermal fluids.